The Chinese-born immigrant infant feeding and growth hypothesis - Kristy A. Bolton; Peter Kremer; Kylie D. Hesketh; Rachel Laws; Karen J. Campbell (BMC, 2016)
Abstract Background Rapid growth in the first six months of life is a well-established risk factor for childhood obesity, and child feeding practices (supplementation or substitution of breast milk with formula and early introduction of solids) have been reported to predict this. The third largest immigrant group in Australia originate from China. Case-studies reported from Victorian Maternal and Child Health nurses suggest that rapid growth trajectories in the infants of Chinese parents is common place. Furthermore, these nurses report that high value is placed by this client group on rapid growth and a fatter child; that rates of breastfeeding are low and overfeeding of infant formula is high. There are currently no studies which describe infant growth or its correlates among this immigrant group. Presentation of hypothesis We postulate that in Australia, Chinese-born immigrant mothers will have different infant feeding practices compared to non-immigrant mothers and this will result in different growth trajectories and risk of overweight. We present the Chinese-born immigrant infant feeding and growth hypothesis - that less breastfeeding, high formula feeding and early introduction of solids in infants of Chinese-born immigrant mothers living in Australia will result in a high protein intake and subsequent rapid growth trajectory and increased risk of overweight and obesity. Testing the hypothesis Three related studies will be conducted to investigate the hypothesis. These will include two quantitative studies (one cross-sectional, one longitudinal) and a qualitative study. The quantitative studies will investigate differences in feeding practices in Chinese-born immigrant compared to non-immigrant mothers and infants; and the growth trajectories over the first 3.5 years of life. The qualitative study will provide more in-depth understanding of the influencing factors on feeding practices in Chinese-born immigrant mothers. Implications of the hypothesis This study will provide evidence of the potential modifiable feeding practices and risk of overweight faced by Chinese-born immigrants living in Australia. This is important to help identify groups at risk of rapid growth and subsequent risk of obesity, to identify opportunities for intervention, and to be able to tailor prevention initiatives appropriately.